Controlled Hydrothermal Synthesis of ZnO Nanorods for High-Performance Gas Sensors - Tangirbergen, Abylay (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2026)
Controlled synthesis of ZnO nanorods with tailored crystallinity and morphology is of great importance for the development of high-performance gas sensors. In this study, ZnO seed layers were deposited on glass substrates by RF magnetron sputtering and subsequently annealed at 400 °C to improve crystallinity and surface uniformity. Hydrothermal growth of ZnO nanorods was then carried out under different precursor concentrations (0.01 M:0.01 M and 1 M:1 M zinc acetate/HMTA) to investigate the effects of solution chemistry on nanorod formation. X-ray diffraction (XRD) revealed a dominant (002) peak in all samples, confirming c-axis oriented growth, while scanning electron microscopy (SEM) demonstrated that higher precursor concentrations yielded longer, densely packed nanorods with well-defined hexagonal cross-sections. The results highlight that both seed layer annealing and precursor concentration strongly influence the structural and morphological evolution of ZnO nanorods. Optimized synthesis conditions lead to vertically aligned, highly crystalline nanorods with increased aspect ratios, which are expected to enhance gas adsorption and electron transport, making them highly suitable for resistive-type gas sensing applications.